QAS 2022
DOI: 10.47750/qas/23.190.36
|View full text |Cite
|
Sign up to set email alerts
|

Ask, Bid, Buy! Online Impulse Buying Behaviour of Ethnic Chinese Mothers in Indonesia

Abstract: The condition of consumer behavior of ethnic Chinese mothers in Indonesia, which has experienced significant changes due to the increasingly massive Covid-19 pandemic, uses the marketplace as a shopping medium. This condition has encouraged commercial growth and economic recovery after the Covid-19 pandemic. In this case, the growth of the modern market that attracts a large number of customers causes consumer purchasing decisions to be more spontaneous. This study aims to analyze the ability of positive emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The combination of these four meta-goals contributes to consumers' decision-making behavior. Aqmala and Putra (2022) revealed that positive emotions were able to mediate the relationship between the influence of shopping style, social factors and sales promotion on online impulse buying. Huang (2005) explored the impact of negative emotions on users' consumption behavior, arguing that negative emotions like boredom will drive away consumers.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The combination of these four meta-goals contributes to consumers' decision-making behavior. Aqmala and Putra (2022) revealed that positive emotions were able to mediate the relationship between the influence of shopping style, social factors and sales promotion on online impulse buying. Huang (2005) explored the impact of negative emotions on users' consumption behavior, arguing that negative emotions like boredom will drive away consumers.…”
Section: Hypothesis Developmentmentioning
confidence: 99%